How do social class position and party preference influence support for fossil fuel taxation in Nordic countries? - Sivonen, Jukka; Koivula, Aki (Taylor and Francis, 2022)
In this paper, we study the influence of the social class and political party preference on support for fossil fuel taxation in Nordic countries. Additionally, we examine how age confounds the relationship between party preference and support for fossil fuel taxation. We utilize Round 8 data from the European Social Survey from Finland, Norway, and Sweden (n = 5021). According to the results, party preference was a more significant factor than social class when explaining citizens’ fossil fuel taxation attitudes. We found attitudinal polarization between Left-Green and Populist Right supporters. Interestingly, we did not find differences between the parties from the traditional left‒right dimension. Also, we found that differences between the Left-Green and Populist Right supporters were more remarkable among the younger cohorts in Sweden. We conclude with a discussion on interconnectivity between new political cleavages and climate policy, which direct the attitudes of a citizen by party preference in particular.